THE EFFECTIVENESS OF THE USE OF THE INTERNET IN THE ORGANIZATION OF A DISTANCE LEARNING SYSTEM - Ortiqov, Olim; Bosimov, Ohun (Science technology&Digital finance, 2023)
The development of the global Internet system has opened Navie prospect for evolutionary development in the global development system. Today, traditional teaching methods are complemented by new teaching methods based on the Internet, e-commerce and telecommunications environment. Distance learning and distance learning via the Internet require a number of new functions, including printing reciprocity, integration and access to the international Internet.